Systemic thermodynamics of soil water - Braudeau, Erik (European Journal of Applied Sciences, 2021)
We show how the systemic approach to represent and model the internal and external organizations of the soil, which is an innovative way in pedology, could have led us to the definition of nested and hierarchical thermodynamic systems and subsystems. Specifically, we review systemic theory of the natural environment, in our case – the representative pedon (the smallest spatial unit in soil science) and its internal organization – namely: the soil horizons, their pedostructure with their two aqueous phases at thermodynamic equilibrium and, finally, the gas and the solid phases. Thereafter, we show how to further deepen the study of the soil hydrostructural properties – by adding two levels of the water molecule organization: both intramolecular – in relation to its atoms – and intermolecular – in relation to other water molecules of the aqueous phase under study. In thermodynamics of soil water, we show how the corrected Gibbs-Duhem equation explains not only results obtained solely by using the systemic approach – considering the Gibbs free energy constancy for each phase related to the solid phase – but also provides an explanation of why in such a case no external energy input or energy exchange should be necessary to ensure the chemical potential variation as a function of water content for each phase in soil. Specifically, we might explain the entropy production without energy exchange, which might be attributable to changes in the atomic vibration amplitudes compensated by the concomitant increases in their vibrational frequencies. Thus, the basic laws of thermodynamics do become apparently visualizable when the soil water evaporates in contact with the surrounding air – just up to the achievement of the pertinent thermodynamic equilibrium.